Pengaruh Penggunaan Power Point Interaktif Terhadap Kemampuan Berpikir Simbolik Anak Usia Dini di TK Tribrata Desa Tupa - Aurike Modati; Icam Sutisna; Pupung Puspa Ardini (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to determine how interactive PowerPoint affects early childhood symbolic thinking skills at Tribrata Kindergarten, Tupa Villiage. This quantitative research uses a pre-experimental design method with one group pre-test and post-test format. The research sample was comprised of 16 children, and a total sampling technique was used. The data collection technique was done using a performance test. The result showed a difference between the ability to think symbolically before and after using interactive PowerPoint. The average numbers before and after the use of interactive PowerPoint media are 11,875 and 19,75. This proved a significant difference before and after treatment. Based on the t-test using paired two samples for means, the tcount value = 10,47 while the ttable value at (α) = 0,05 or 2,131; therefore, tcount>ttable or 10,47>2,131. since tcount>ttable, the H0 is rejected and H1 is confirmed, which means there was an effect between the use of interactive PowerPoint on the symbolic thinking skills of early childhood at Tribrata Kindergarten, Tupa Village.